Enter the Dragon: Have Imports from China Hurt Wages in Manufacturing?1. Issue 3 (3rd September 2013) - Posso, Alberto
<x xml:space="preserve">Abstract</x> While it is often argued that imports from China are depressing manufacturing wages in recipient countries, this has never been tested using cross‐country data. This article investigates the effect of increased import penetration from China on the wages of workers (total, skilled and unskilled) in the manufacturing sector of 100 economies from 1976 to 2008. The econometric analysis finds no evidence suggesting that import penetration of manufactured goods from China has a statistically significant effect on real manufacturing wages (skilled, unskilled and total) in either developed or developing economies. This may be because Chinese exports are too heterogeneous to strongly affect any particular industry in recipient economies or because foreign consumers are differentiating products made in China from those made locally based on country and brand loyalty and preconceived notions of quality.